REKONSTRUKSI EPISTEMOLOGI KEILMUAN ISLAM KONTEMPORER Telaah Pemikiran Epistemologi Ilmuan Muslim Kontemporer: Perspektif Intelektual Muslim Indonesia. - Hermanto, Mulyadi (Universitas Muhammadiyah Tapanuli Selatan, 2016)
Reconstruction Epistemology Islamic Contemporer.Secularization of science, dichotomy of knowledge, and degradation of islamic knowledge in the modern era had stimuled some intelectual discources in indonesia Moslem intellectual community. They have payed affention to reconstruct integrally the paradigma of islamic knowlegde in medern era. At least, in this context, there are three types of integration of islamic knoelgde in discources of muslim intellectual in Indonesia, such as: revitalismintegrative, interconnective-integrative, and transformativeintegralistic. Nevertheless, these intellectual efforts had been on going process and formation in order to find the ideal model of islamization of knowledge that are compatible toislamic, modernism, and indonesian velues